Effects of cannabinoids on ligand-gated ion channels - Oz, Murat; Yang, Keun-Hang Susan; Mahgoub, Mohamed Omer (Frontiers in Physiology, 2022)
Phytocannabinoids such as Δ9-tetrahydrocannabinol and cannabidiol, endocannabinoids such as N-arachidonoylethanolamine (anandamide) and 2-arachidonoylglycerol, and synthetic cannabinoids such as CP47,497 and JWH-018 constitute major groups of structurally diverse cannabinoids. Along with these cannabinoids, CB1 and CB2 cannabinoid receptors and enzymes involved in synthesis and degradation of endocannabinoids comprise the major components of the cannabinoid system. Although, cannabinoid receptors are known to be involved in anti-convulsant, anti-nociceptive, anti-psychotic, anti-emetic, and anti-oxidant effects of cannabinoids, in recent years, an increasing number of studies suggest that, at pharmacologically relevant concentrations, these compounds interact with several molecular targets including G-protein coupled receptors, ion channels, and enzymes in a cannabinoid-receptor independent manner. In this report, the direct actions of endo-, phyto-, and synthetic cannabinoids on the functional properties of ligand-gated ion channels and the plausible mechanisms mediating these effects were reviewed and discussed.